Psychophysiological indices of cognitive style: A triangulated study incorporating neuroimaging, eye-tracking, psychometric and behavioral measures. (1st July 2019) - Bendall, Robert C.A.; Lambert, Sarah; Galpin, Adam; Marrow, Lynne P.; Cassidy, Simon
Abstract: Employing a triangulated design to explore psychophysiological indices of cognitive style, the study investigated the validity of the intuition-analysis dimension of cognitive style and its associated construct measure, the Cognitive Style Index (CSI). Participants completed a comparative visual search (CVS) task whilst changes in hemodynamic concentrations in the prefrontal cortex (PFC) were monitored using functional near-infrared spectroscopy and eye movements were recorded together with task performance measures of response time and accuracy. Results revealed significant style-related differences in response time and number of saccades. Analysts were characterized by fewer saccadic eye movements and quicker response times—but with comparable accuracy scores—compared to intuitives, suggesting a more efficient visual search strategy and decision-making style on the experimental task. No style-related differences in neural activation were found, suggesting that differences were not mediated by style-specific variations in brain activation or hemispheric lateralization. Task-evoked neural activation—compared with baseline resting state—represented the value of PFC-based neural activation measures in studies of cognitive processing. Findings demonstrated style-related differences supporting the intuition-analysis dimension of cognitive style and the validity of the CSI as a psychometric measure of style. The potential value of valid psychometric measures of cognitive style in applied areas is highlighted. Highlights: Cognitive style associated with differences when completing a visual search task. Analysts exhibit a more efficient visual search strategy and decision-making style. Cognitive style does not affect accuracy scores on a visual search task. No style-specific variations in brain activation or hemispheric lateralization. Intuition-analysis dimension measured by the Cognitive Style Index is supported.